PWE-122 Determinants Of Weight Loss Prior To Diagnosis In Inflammatory Bowel Disease: A Retrospective Observational Study. (9th June 2014) - Alexakis, C; Elsherrif, Y; Mendall, M
Abstract : Introduction: Weight loss is a recognised presenting feature of Inflammatory Bowel Disease (IBD) and considered as marker of malnutrition and disease severity. This is well established in children with IBD, however in adults, evidence based data is lacking. There is little in the literature characterising weight loss prior to formal diagnosis, or defining the disease factors associated with it. Methods: Patients with IBD attending outpatient clinic were provided with a questionnaire enquiring into various aspects of their disease. Percentage Body Mass Index loss prior to diagnosis was calculated for each subject. Patients were sub-categorised into groups according to severity of % BMI loss (insignificant <5%, moderate 5–10%, severe 10–20%, extreme >20%), and disease and patient factors associated with weight loss were determined. Results: 494 subjects were recruited. 237 had Crohn's Disease (CD); 257 had Ulcerative Colitis (UC). Mean%BMI loss prior to diagnosis was greater in CD (CD 9.76% vs UC 7.63, p = 0.02). Increasing age at diagnosis was inversely associated with weight loss prior to diagnosis in UC (–0.1 per year of age, 95% CI -0.17 – -0.03, p = 0.004), and CD (-0.15 per year of age, 95% CI -0.23 – -0.06, p = 0.003). In CD, patients with prior appendectomy had reduced risk of weight loss (HR 0.38, p = 0.014). Ileal disease was a risk factor in patients with extreme weight loss. Conclusion: Weight loss is a significant problem for many IBD patients at presentation, especially in younger age and Crohn's disease with ileal involvement. Improved awareness of the presenting features of IBD should encourage wider use of malnutrition screening tools and earlier investigative tests to uncover patients at risk. Appendectomy confers a protective effect in CD. Disclosure of Interest: None Declared.